Altered microbiome and metabolome profiling in fearful companion dogs: An exploratory study. - Luigi Sacchettino; Michele Costanzo; Iolanda Veneruso; Valeria D'Argenio; Maria Mayer; Francesco Napolitano; Danila d'Angelo (PLoS ONE)
Behavioral dysfunctions in dogs represent one of the main social concerns, since they can endanger animals and human-dog relationship. Together with the trigger stimulus (human, animal, place, scent, auditory stimuli, objects), dogs can experience stressful conditions, either in multiple settings or unique situations, more often turning into generalized fear. Such a dysfunctional behavior can be associated with genetic susceptibility, environmental factors, traumatic experiences, and medical conditions. The available therapy, based on behavior approaches, environmental management, and neurochemical manipulation, through nutrition, supplements, medicines, and pheromones, represent the mainstays of the treatments currently accessible. Growing evidence in humans and animals highlight the importance of the gut-brain axis in the modulation of the brain physiology and behavior as well. Here, taking advantage of the next generation sequencing approach, we sought to investigate the potential connection between gut microbiota and microbiome in dogs suffering from generalized fear (n = 8), when compared to healthy subjects (n = 8), who all lived in different families. Faecal microbiota evaluation showed a differential abundance of taxa related to Proteobacteria and Firmicutes Phyla, between case and control dogs. Moreover, serum metabolomics documented significant alterations of molecules associated to GABA and glutamate neurotransmission in the patients, as well as bile acids metabolism. Overall, our preliminary and integrated investigations highlighted an intriguing role for the microbiome-metabolome network, allowing to further unveil the potential pathophysiology of relational issues in companion animals and paving the way for more effective therapeutical approaches.